Programmed ventricular stimulation in patients with active vs previous arrhythmic myocarditis. (3rd February 2020) - Peretto, Giovanni; Sala, Simone; Basso, Cristina; Della Bella, Paolo
Abstract: Introduction: No studies so far addressed the role of invasive programmed ventricular stimulation (PVS) in myocarditis patient's arrhythmic risk stratification. Methods and Results: We present a single‐center prospective study on 96 consecutive adult patients (44 ± 13 years, 70.1% males) with myocarditis and ventricular arrhythmias (VA) at index hospitalization. Depending on baseline endomyocardial biopsy (EMB) and cardiac magnetic resonance, patients were divided into two groups: active (A) vs nonactive (NA) myocarditis. All of the patients underwent PVS at index hospitalization. Medical treatment and implantable cardioverter‐defibrillator (ICD) implantation were clinically‐driven. Malignant VA episodes (MVA = ventricular tachycardias [VT], ventricular fibrillation [VF], appropriate ICD therapy) were evaluated at 54 ± 18 months follow‐up (FU). Patients who underwent VT ablation or with myocarditis recurrence (n = 9) were excluded. Of 87 patients, 41 (47.2%) were in group A. PVS was positive in 32 cases (36.8%), 16 A vs 16 NA ( P  = NS), with no associations with VA type at presentation. Before discharge, 55 patients (63.2%) underwent ICD implant. In FU, MVA occurred in 27 patients (31.0%), 13 A vs 14 NA ( P  = NS), 18 PVS+ vs 9 PVS‐ ( P  < .001). The association between PVS result and FU MVA was maximal in group NA (high rule‐out performance with negative predictive value = 90.0%, P  < .001) and minimal in group A (low rule‐in performance with PPV = 43.8%, P  = .302). In the whole population, three independent factors for major VA were identified: major arrhythmic onset by sustained VT or VF (HR 2.8, 95% CI, 1.0‐7.4, P  = .042), presence of fibrosis at EMB (HR 5.8, 95% CI, 1.1‐30.0, P  = .038), and PVS positivity (HR 4.2, 95% CI, 1.7‐10.7, P  = .003). Conclusion: In myocarditis patients presenting with VA, PVS is associated with FU MVA in NA patients, but not in A ones. Overall, risk stratification of arrhythmic myocardits is still complex and multifactorial.